2015
DOI: 10.5194/bg-12-977-2015
|View full text |Cite
|
Sign up to set email alerts
|

Frozen ponds: production and storage of methane during the Arctic winter in a lowland tundra landscape in northern Siberia, Lena River delta

Abstract: Abstract. Lakes and ponds play a key role in the carbon cycle of permafrost ecosystems, where they are considered to be hotspots of carbon dioxide CO 2 and methane CH 4 emission. The strength of these emissions is, however, controlled by a variety of physical and biogeochemical processes whose responses to a warming climate are complex and only poorly understood. Small waterbodies have been attracting an increasing amount of attention since recent studies demonstrated that ponds can make a significant contribu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(86 citation statements)
references
References 45 publications
4
82
0
Order By: Relevance
“…Based on yearround eddy flux measurements of methane emissions from Alaskan Arctic tundra sites, Zona et al (2016) find that cold season (September to May) emissions account for ≥ 50 % of the annual methane flux, with the highest emissions from non-inundated upland tundra. They find a major fraction of cold season emissions occur during the "zero curtain" period, when subsurface soil temperatures are near 0 • C. Langer et al (2015) report winter emissions from tundra ponds in Siberia as they are freezing during early winter. They analyzed concentrations of methane in bubbles (trapped in the lake ice), which were higher at depths than at the ice surface.…”
Section: Regional Evaluation Over West Siberian Lowlandsmentioning
confidence: 99%
“…Based on yearround eddy flux measurements of methane emissions from Alaskan Arctic tundra sites, Zona et al (2016) find that cold season (September to May) emissions account for ≥ 50 % of the annual methane flux, with the highest emissions from non-inundated upland tundra. They find a major fraction of cold season emissions occur during the "zero curtain" period, when subsurface soil temperatures are near 0 • C. Langer et al (2015) report winter emissions from tundra ponds in Siberia as they are freezing during early winter. They analyzed concentrations of methane in bubbles (trapped in the lake ice), which were higher at depths than at the ice surface.…”
Section: Regional Evaluation Over West Siberian Lowlandsmentioning
confidence: 99%
“…In permafrost regions, a continuously unfrozen layer (talik) may develop underneath such deeper waterbodies, which strongly affects carbon cycling in these sediments (Schuur et al, 2008). Several studies have shown a positive correlation between waterbody surface area and depth (Langer et al, 2015;Wik et al, 2016). However, there is large variability in the areadepth relationship, i.e., there are large but shallow lakes that freeze to the bottom and small but deep ponds that develop a talik, and these characteristics may also change over time with changes in water level and basin morphology.…”
Section: Definition Of Ponds and Lakesmentioning
confidence: 99%
“…Arctic ponds are characterized by intense biogeophysical and biogeochemical processes. They have been identified as a large source of carbon fluxes compared to the surrounding terrestrial environment (Rautio et al, 2011;Laurion et al, 2010;Abnizova et al, 2012;Langer et al, 2015;Wik et al, 2016;Bouchard et al, 2015). Due to their small surface areas and shallow depths, ponds are especially prone to change; various studies reported ponds drying out or increasing in abundance due to new thermokarst or the drainage of large lakes (Jones et al, 2011;Andresen and Lougheed, 2015;Liljedahl et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…4.2.1) challenging. Furthermore, small water bodies and lakes can strongly modify the ground thermal regime both in the underlying ground and in the surrounding land areas Langer et al, 2015), so the model results are questionable in areas with a high fraction of open water areas (Muster et al, 2012). While more sophisticated model schemes (Plug and West, 2009;Westermann et al, 2016) can simulate the ground thermal regime of such features, a spatially distributed application is challenging: in general, higher-complexity models require additional input data and model parameter sets (e.g., precipitation for a water balance model, Endrizzi et al, 2014), for which the spatial and temporal distributions are poorly known.…”
Section: The Cryogrid 2 Modelmentioning
confidence: 99%